Biology and Management of the Rice Stink Bug (Hemiptera: Pentatomidae) in Rice, Oryza sativa (Poales: Poaceae). Issue 1 (8th May 2021) - Bhavanam, Santhi; Wilson, Blake; Blackman, Bryce; Stout, Michael
Abstract: The rice stink bug, Oebalus pugnax (Fabricius), is the most important late-season insect pest of rice in the southern United States. Nymphs and adults feed on rice grains, resulting in losses in yield and grain quality. Aspects of the biology, ecology, life history, and chemical ecology have been investigated in southern rice producing states but several outstanding questions remain. Standard economic threshold levels (ETLs) based on sweep net sampling for rice stink bug have been established depending on grain development stage and geographic location. However, recent studies on the relationship between rice stink bug densities, feeding damage, and its economic impacts suggests that changes to ETLs for rice stink bug may be needed. The primary management tactic for controlling rice stink bug infestations is the application of chemical insecticides, but alternative management tactics are needed because of the potential for development of insecticide resistance and impacts on non-target organisms. Biological control appears to be a promising strategy, even though it has remained largely untapped. Future research should focus on the biology, behavior, host plant preference, and chemical ecology of the rice stink bug, knowledge of which will aid in the development of integrated pest management strategies. This review article covers the biology, feeding behavior, sampling techniques, ETLs, management, knowledge gaps, and potential management tactics of rice stink bug.